754 STEEP RAMP TEST: AN ALTERNATIVE TO ASSESS PHYSICAL FITNESS BEFORE OESOPHAGECTOMY IN CANCER PATIENTS. (17th September 2021) - Crull, David; Mekenkamp, I; Ruinemans, G M F; Det, M J; Kouwenhoven, E A
Abstract:  : Oesophagectomy patients are at high risk of perioperative complications. An important predictor for a complication is inadequate preoperative physical fitness. Cardiopulmonary Exercise Test (CPET) is the golden standard for measuring VO₂ max. The Steep Ramp Test (SRT) is an alternative with a lower patient burden and cost, but provides an estimation of VO₂ max. The aim was to determine whether SRT is an adequate alternative for CPET to determine preoperative fitness in oesophageal cancer patients. Methods: The population consisted of 113 oesophageal cancer patients of a single centre that have performed CPET and SRT within a timeframe of two weeks. The agreement between SRT and CPET was analysed using a t-test, the Pearson correlation, the Intraclass Correlation Coefficient (ICC) and the Bland-Altmann analysis. A CPET-measured VO₂ max of 17 mL/kg/min was the set threshold for adequate operative fitness, based on current literature. Results: The mean difference between the CPET and SRT was 2.77 mL/kg/min (95% CI, 2.14–3.41). The Pearson correlation was 0.792 (P < 0.001). The ICC was 0.879 (95% CI, 0.825–0.917). In 93 (82.3%) patients, SRT was higher than the CPET. The limits of agreement (LOA) for the Bland-Altmann were − 3.89 − +9.44. Thirty-one (27.4%) patients performed better on SRT than the set threshold plus the upper LOA. Twenty-three patients scored inadequate on CPET, of whom 14 patients (60.9%) SRT was sufficient. Conclusion: VO₂ max as estimated by SRT differs from the VO₂ max as measured by CPET. In patients that are well above the threshold of adequate preoperative fitness, the difference is of clinical irrelevance. In conclusion: SRT is a promising alternative to CPET for determining preoperative physical fitness, it might render CPET obsolete for fit individuals which leads to a lower burden for the patient and substantial cost reduction.